Access to the European cultural heritage of settlements and towns in the Danube macro-region through interoperable strategies digital transformation - Babin ANATOLIE; Elena PRUS; Elena MARGINEANU (Smart Cities and Regional Development Journal)
Tangible cultural heritage is a strategic resource for the development of rural and urban settlements. Cooperation with stakeholders from EU countries and regions within the Danube macro-region, such as cultural heritage institutions and competent authorities, allows to agree on the preparation and adaptation of compatible digital innovation strategies in local initiative groups in the Republic of Moldova and Ukraine, as well as on impact mapping through a set of pan-European socio-economic indicators. Objectives of the study: to analyse the available European best practices and methodology for adaptation in the integration of the regions of the Republic of Moldova and Ukraine in the interregional innovation partnership on the smart specialisation "Cultural and Creative Regional Ecosystems" (CCRE-S3) [1]. The overall horizontal objective of the integration into the platform should be to add value to the common characteristics of the cultural and creative sector and to create a permanent discovery mechanism that will carry out activities to identify strategic investments and the use of innovation transfer tools. Previous works: previous concept, research and experience are described in the articles [2] and [3]. Approach: European benchmarking, comparative analysis, bibliographic research. Outcome: recommendations aimed at stimulating new ideas and opportunities related to cultural and creative experiences for local communities and residents by involving several groups of professions that use, apply and implement new technologies in the cultural and creative industries sector. The European Programmes provide resources to support their implementation. In this way, the Danube Strategy participating States [4],  by supporting partnerships between the cultural heritage sector and other sectors such as higher education and vocational education and training, creative industries and sustainable cultural tourism, will be able to stimulate innovation for new services and applications in their regions.